2007
DOI: 10.1007/s00441-007-0524-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a non-neuronal cholinergic system and occurrence of up- and down-regulation in expression of M2 muscarinic acetylcholine receptors: new aspects of importance regarding Achilles tendon tendinosis (tendinopathy)

Abstract: Limited information is available concerning the existence of a cholinergic system in the human Achilles tendon. We have studied pain-free normal Achilles tendons and chronically painful Achilles tendinosis tendons with regard to immunohistochemical expression patterns of the M(2) muscarinic acetylcholine receptor (M(2)R), choline acetyltransferase (ChAT), and vesicular acetylcholine transporter (VAChT). M(2)R immunoreactivity was detected in the walls of blood vessels. As evidenced via parallel staining for CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 52 publications
7
68
1
Order By: Relevance
“…Scarring in turn may lead to impaired circulation with mechanical constriction until the obliteration of neovessels: in 20-50% of long-lasting tendinopathy patients no neovascularization is found [128,129] . This reduction in blood flow may also be explained by the fact that pathological tendons exhibit a decreased occurrence of sympathetic nerve fibres: the reduction in vasoregulatory noradrenalin causes vasoconstriction [105] . Nerve however will survive causing persistence of pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarring in turn may lead to impaired circulation with mechanical constriction until the obliteration of neovessels: in 20-50% of long-lasting tendinopathy patients no neovascularization is found [128,129] . This reduction in blood flow may also be explained by the fact that pathological tendons exhibit a decreased occurrence of sympathetic nerve fibres: the reduction in vasoregulatory noradrenalin causes vasoconstriction [105] . Nerve however will survive causing persistence of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, however, it is conceivable that inflammation and degeneration are not mutually exclusive: tendons respond to repetitive overload beyond physiological threshold by either inflammation of their sheath, degeneration of their body, or a combination of both [102,103] ; inflammation has been shown to play its role mainly in early human tendinopathy, while in the late phase of tendinopathy degeneration gradually occurs. Over time, possibly due to the lack of blood vessels within the tendon, instead of a chemical, a neurogenic inflammatory process takes place [104,105] .…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal immunoreaction to choline acetyltransferase, vesicular acetylcholine transporter and acetylcholinesterase in tendons is reported to be limited compared to other tissues investigated. However, whether cholinergic innervation in tendinopathy is significantly lower than that of healthy tendons is still unclear (66,67,140).…”
Section: Parasympathetic Innervationmentioning
confidence: 99%
“…Immunohistochemical studies have identified activated markers of cellular acetylcholine production in human tendinopathy, most prominently seen in morphologically altered tenocytes (66,67,140). Immunoreaction to choline acetyltransferase and vesicular acetylcholine transporter has recently been detected in normal Achilles tenocytes (141).…”
Section: Parasympathetic Innervationmentioning
confidence: 99%